Thinking fast and slow: Testing cognitive expertise in high division and lower division field hockey players - de Vries, S. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: A number of studies showed that expert athletes outperform less experienced athletes on a number of cognitive domains (Mann, Williams, Ward, & Janelle, 2007). Although most of this work was initially aimed at studying the relationship between sport expertise and performance on game specific cognition recent studies also explored the relationship between expertise and executive functioning (Alves et al., 2013). Positive results of expert athletes on executive functioning could also be explained by the fact that executive functioning tests rely on psychomotor speed and expert athletes often have fast response times. With this study we wanted to answer the question whether differences would exist between high and lower division field hockey athletes and whether these differences would be independent of psychomotor speed. Method: 30 high division field hockey players (16.5 years; 15 male, national main division) and 30 lower division field hockey players (16.8 years; 15 male, national first division) participated in the study. All athletes completed two executive functioning tests: the Figure Fluency Test (FFT) and a digital version of the Trail Making Test (TMT part A and B). A Finger Tapping Task (FTT) was used to measure psychomotor speed. Both, the TMT and the FTT were administered with a digital tablet. Differences between high and lower division and male and female athletes were tested with an ANOVA. The influence of psychomotor speed on cognitive test performance was tested with an ANCOVA with FTT as a covariate. Results: High division athletes were significantly better then lower division athletes on the TMT A with F(1,59) = 23,13, and TMT B with F(1,59) = 7,33 and FFT with F(1,59) = 5,99 (all p <.05). Performance on the difference score between TMT A and TMT B (TMT B-A) did not differ significantly with F(1,59) = 0,11, p =.74. When corrected for psychomotor speed only performance on the FFT differed significantly between high and low division athletes with F(1,57) = 4,22, p <.05. Discussion: Our research shows that psychomotor speed influences performance on cognitive measures in high and low division field hockey players. After taking psychomotor speed into account high division athletes performed significantly better on the FFT while performance